AI UTILIZATION IN LANGUAGE LEARNING: INVESTIGATING THE MOTIVES AND IMPACT OF ARTIFICIAL INTELLIGENCE ON STUDENTS’ WRITING SKILLS - Ariski, Yofi; Muluk, Safrul (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
The purpose of this study is to investigate the motives for using AI (Artificial Intelligence) and its impact on the writing skills of EFL (English as a Foreign Language) students. Using mixed methods, this study involved 30 active EFL students. Data were collected through a Likert scale questionnaire to measure the motives for using AI and a writing test before and after using AI. The results showed that the main motives for using AI were to improve writing quality (85%), to help in the editing process (78%), and to increase time efficiency (72%). The analysis of writing skills showed significant improvements in organization (+25%), vocabulary (+30%), and grammar (+28%). However, there was a decrease in originality (-15%). The implications of this study provide new insights into the integration of AI in language learning and the importance of balancing the use of technology with the development of independent writing skills. Keywords:  Artificial Intelligence, writing skills, EFL learning, motives for using AI